Fragment N2, a caspase‐3‐generated RasGAP fragment, inhibits breast cancer metastatic progression. Issue 1 (4th March 2014) - Barras, David; Lorusso, Girieca; Lhermitte, Benoît; Viertl, David; Rüegg, Curzio; Widmann, Christian
<x xml:space="preserve">Abstract</x> The p120 RasGAP protein negatively regulates Ras via its GAP domain. RasGAP carries several other domains that modulate several signaling molecules such as Rho. RasGAP is also a caspase‐3 substrate. One of the caspase‐3‐generated RasGAP fragments, corresponding to amino acids 158–455 and called fragment N2, was previously reported to specifically sensitize cancer cells to death induced by various anticancer agents. Here, we show that fragment N2 inhibits migration in vitro and that it impairs metastatic progression of breast cancer to the lung. Hence, stress‐activated caspase‐3 might contribute to the suppression of metastasis through the generation of fragment N2. These results indicate that the activity borne by fragment N2 has a potential therapeutic relevance to counteract the metastatic process.